Aanbid die godsdienste dieselfde God? - Buitendag, Johan (Hervormde teologiese studies, 1994)
Do all religions pray to the same God? A highly debated matter in South African religopolitical field is the question of whether different religions may worship together and if they pray to the same god at all. This question has come to the fore during the negotiation phase for a new governmental dispensation in this country, as well as in the opening prayers for Parliament in a pluralistic society. An exposition of the different views is given. The author opts for a view of existential experience of the personal, revealed, One and Only God. This conviction gives us the confidence in the Gospel so indispensable to the life of our churches in a pluralistic context. The dichotomy between subjectivity and objectivity is being rejected as is the consequent attitude of timidity or of anxiety on the part of the Christians in South Africa. A distinction should be made between worship in the church and prefers in a worldly situation.